Pengaruh Pelatihan Otonomi terhadap Tingkat Otonomi Siswa Sekolah Menengah Atas di Bandung - Sulisworo Kusdiyati; Yuli Aslamawati; Dwi Agustin Nuraini Sirodj (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2018)
High school students in the city of Bandung appeared to have moderate or even low learning engagement. This low level of learning engagement was caused by low sense of autonomy. Therefore, to increase learning engagement, an autonomy training program is needed for these students. This study aimed to find out whether the autonomy training program increases the autonomy level of students. The design of the study was quasi-experimental with the one-group before-after design. The research subjects were collected using random sampling technique, with a total of 37 students from two high schools in Bandung. The Autonomy instrument was collected using a questionnaire compiled by researchers based on Ryan and Deci’s Self-determination theory. Based on the validity and reliability test, the instrument was valid and reliable. The results showed that autonomy training is effective in enhancing students' sense of autonomy.